Impact of pesticides on food: A literature review (Research, Society and Development, 2021)
Brazil is the largest consumer of pesticides in the world. The use of these pesticides alters the composition of flora and fauna, preserving food from the harmful effects of some living beings. However, its indiscriminate use can damage human health and the environment. The aim of the present study was to analyze the risks caused to man by the consumption of food with pesticide residues. It is an integrative literature review, with electronic searches in the Scielo (Scientific Electronic Library Online) and Virtual Library databases of original articles published in the last eight years. Regarding pesticides, the study found that, in addition to the diversity of those used in food production, many are handled incorrectly and in quantities above those allowed. The residues of these compounds are found in many foods of plant origin present on the table of the majority of the Brazilian population and can cause harmful effects, acute or chronic, depending on the type of pesticide and the time of exposure to it. There are several actions used to minimize the effects of pesticides, such as greater supervision in commercialization and handling and encouraging the consumption of organic products from family farming.